Preference for primary care in Chinese homebound patients - Jinxin Zhang; Xiaojie Sun; Aaron Yao (BMC, 2024)
Abstract Objective This study aims to describe the preference for primary healthcare (PHC) and investigate associated factors among homebound residents in both rural and urban areas of China. It provides valuable insights to facilitate the rational allocation of healthcare resources and promote the utilization of PHC. Methods In this nationally representative cross-sectional study, we utilized the most recent data (2020) from the China Family Panel Studies (CFPS). Participants were recruited from 25 provincial-level administrative regions in both rural and urban areas of China. Homebound patients were asked to provide details about their individual characteristics, variables related to family caregiving, and preferences for PHC. Multivariable logistic models were used to analyze potential factors associated with preference for PHC. Estimates of association were reported as odds ratios (OR) and their 95% confidence intervals (CI). Results The study found that 58.43% of rural patients reported a preference for PHC, while 42.78% of urban patients favored PHC. Compared to rural participants who did not received inpatient care in the past year, those who received inpatient care in the past year had 67% lower odds of choosing PHC (OR:0.33, 95% CI:0.19-0.59); Compared to rural participants who did not received family caregiving when ill, those who received family caregiving when ill had 59% lower odds of choosing PHC (OR: 0.41, 95% CI:0.21-0.77). Correspondingly, Compared to urban participants who did not received inpatient care in the past year, those who had received inpatient care in the past year had 75% lower odds of choosing PHC (OR: 0.25, 95% CI: 0.10-0.56); Compared to urban participants who did not received family caregiving when ill, those who received family caregiving when ill had 73% lower odds of choosing PHC (OR: 0.27, 95% CI: 0.11-0.63); Compared to urban participants who with agricultural Hukou, those with Non-agricultural Hukou had 61% lower odds of choosing PHC (OR: 0.39, 95% CI:0.18-0.83); Compared to urban participants living in the eastern part of mainland China, those living in the central part of China had 188% higher odds of choosing PHC (OR: 2.88, 95% CI: 1.14-7.29). Conclusion Policymakers should focus on tailoring PHC to vulnerable populations and prioritizing family-based public health strategies for enhancing homebound patients' perceptions of PHC. Furthermore, further study is needed on whether the Hukou registration system affects the barriers that homebound patients experience in choosing healthcare providers.